The behavior characteristics of a reservoir levee subjected to increasing water levels - Lee, Chung-Won; Kim, Yong-Seong; Park, Sung-Yong; Kim, Dong-Gyun; Heo, Gunn (Journal of Civil Engineering and Management, 2017)
Centrifugal model testing has been widely used to study the stability of levees. However, there have been a limited number of physical studies on levees where the velocity of increasing water levels was considered. To investigate the behavior characteristics of reservoir levees with different velocities of increasing water levels, centrifugal model tests and seepage-deformation coupled analyses were conducted. Through this study, it was confirmed that increasing water levels at higher velocities induces dramatic increases in the displacement, plastic volumetric strain and risk of hydraulic fracturing occurring in the core of the levee. Hence, real-time monitoring of the displacement and the pore water pressure of a levee is important to ensure levee stability.